A new species of annual fish, Hypsolebias tocantinensis sp.n. (Cyprinodontiformes:Rivulidae) from the rio Tocantins basin, northeastern Brazil - Nielsen, Dalton Tavares Bressane; Cruz, João Carlos; Junior, Arsênio Caldeira Baptista (Zootaxa, 2012)
Hypsolebias tocantinensis n. sp. is described from a temporary pool located in the rio Tocantins basin, Maranhão stateBrazil. Hypsolebias tocantinensis belongs the H. flammeus species-group. It is the first occurrence of genus Hypsolebiasin Maranhão state. This new species differs from all other species of that group, except Hypsolebias flammeus (Costa,1989), Hypsolebias multiradiatus (Costa &Brasil, 1994) and Hypsolebias brunoi (Costa, 2003), by male color pattern andby the presence of a metallic blue sheen surrounding the black spots in the female. It differs from H. flammeus, H. multi-radiatus and H. brunoi by the shape of the dorsal and anal fins (rounded vs. pointed) and by the orientation of the reddishbrown bars in males (diagonal vs. vertical). Hypsolebias tocantinensis differs from all other Hypsolebias by the presenceof, in females, irregular light brown stains on the anal fins and by the pattern of the metallic blue sheen around the blackspots (completely surrounding the black spots while in congeners this blue sheen is either absent or present in vertical bars).